Deteksi coronavirus pada kelelawar di Kabupaten Lamongan - Muhammad Badrut Tamam; Aisyah Hadi Ramadani; M. Ainul Mahbubillah (Livestock and Animal Research, 2022)
Objective: To obtain information about the presence of coronavirus in bats to find potential of new disease reservoir as well as not yet reported disease reservoir in Lamongan District. This research can be used by the government as a basis for planning and evaluating disease control programs and for researchers it can be used for vaccine and drug design, viral phylogenetic, analysis of viral distribution, and viral databases.Methods: Sampling was carried out at 3 points representing different habitat types. The first point is at Pucakwangi Cave Babat Lamongan, the second is at Paciran Lamongan beach area, and the last is at the Mantup Forest Lamongan. Sampling was carried out using a mist net with the help of local workers. The netted bats were caught and put in a bag. Parameters observed included gender, morphometry, species, and detection of the presence of coronavirus. Detection of the virus using the oropharyngeal swab method, then the RNA samples were tested by RT-PCR and sequencing. The primer used to detect the coronavirus is primer forward 5′-CACGCAACTTGTTGTAATGCGT CAGAGA-3′ and primer reverse 5′- CACGTGCTTTTGCAGGCACTATACGAC-3′.Results: Five species of bats obtained from 3 sampling locations namely Taphozous melanopogon, Chaerophon sp., Hipposideros sp., Cynopterus sp., Macroglossus sp. RT-PCR test of sample G1, G6, G8, P1, P2, P3, H1, H3, and H6, shows that no coronavirus from DNA sample amplified.Conclusions: Negative result of Coronavirus detection by molecular analysis is not an indicator of no potential of species Taphozous melanopogon, Chaerophon sp., Hipposideros sp., Cynopterus sp., and Macroglossus sp. as a Coronavirus reservoir. Increasing the number of samples and expansion of study area still needed to obtain more comprehensive data.